Recent progress in the development of new artificial metalloenzymes as biocatalysts for selective oxidations and Diels‐Alder reaction ‐ Mini‐Review. Issue 4 (26th August 2020) - Avenier, Fréderic; Ghattas, Wadih; Ricoux, Rémy; Mahy, Jean‐Pierre
Abstract: Our recent research is turning towards the elaboration of artificial metalloenzymes that catalyze reactions of interest for organic chemistry under eco‐compatible conditions. First, totally artificial metalloenzymes that catalyze selective oxidations in water are described following three main lines: (i) Insertion of microperoxidase 8 into Metal Organic Frameworks leading to artificial metalloenzymes as new biocatalysts for the selective sulfoxydation of sulfides and oxidation of dyes and by H2 O2 ; (ii) Design of a new polyimine polymer‐based artificial reductase that allows the reductive activation of dioxygen and its use as an oxygen atom source for selective oxidations catalyzed by metal complexes including metalloporphyrins, copper complexes or Polyoxometalates and, (iii) Design of new artificial metalloenzymes that catalyze the photoreduction of H2 O in the presence of photoactivable ruthenium complexes and the concommitant oxidation of sulfides. Second, the synthesis of new stereoselective Diels‐Alderases is described following three strategies: (i) Covalent insertion of metal complexes into thermostable artificial proteins issued from a new family of alpha‐helical repeated motifs (αReps), (ii) Substitution of the native Fe ion of a cupin‐like protein, ACCO oxidase, by a copper(II) ion and (iii) Insertion of a copper(II) complex‐antagonist conjugate into an adenosine receptor located at the surface of living HEK cells.